Internationalized Satellite Internet Business Operation Platform - Wenlong ZENG; Shuang ZHAO; Shaopeng CHEN; Tao JIN; Chang JIANG (天地一体化信息网络)
Through quantitative analysis of the business market prospects for satellite internet and analyses of international business operation service models, the study explained the necessity of conducting satellite internet operation service.Therefore, further research on how to establish an internationalized satellite internet business operation platform becomes particularly important.On this basis, it primarily discussed a mid-tiered architecture with flexibly and scalability for the operation platform, proposes a tiered collaborative deployment architecture and mechanism for international operations, conducts research on multi-tenant management methods for global market operations, and suggests a roadmap for the integration of satellite internet operators with ground operators, which is providing valuable guidance for the future development of satellite internet operation platform.